Determination Contents of Total Phenolic Pigments and Spectrophotometric Characterization of Crude Extracts of Ten Tinctorial Plants of Niger which is Usable in Solar Energy - Moutari, Souley Kallo; Abdoulkadri, Ayouba Mahamane; Boulhassane, Abdourahamane Saidou; Rabani, Adamou; Khalid, Ikhiri (European Scientific Journal, ESJ, 2018)
Dye Sensitized-Solar Cells (DSSCs) have been extensively investigated because of their environmental friendliness and low production cost. At the heart of these is the photosensitive pigment that plays a key role in the collection of sunlight radiations and its conversion into electrical energy. However, the toxicity and the cost of pigment synthesis limit the increased use of these prototypes. Natural pigments can be an effective, sustainable, and inexpensive alternative. This paper focuses on determining the main phenolic pigments contents and evaluating the solar light collection capacity of ten (10) tinctorial plants crude extracts, via UV-Visible Spectrophotometry. High concentrations of total polyphenols (46.54 mgEqAG/g), flavonoids (10.95 mgEqQuer/g), anthocyanins (181.9 mgL-1 ), and tannins (40.1 mgL-1 ) were recorded in some extracts of these plants. Absorption spectra showed intense absorption domains around 280 nm in the ultraviolet (UV), and also in the visible (400 to 700 nm). These absorptions would be attributed to the π-π* and n-π* electron transitions of the chromophores present in the anthocyanin, flavonoid, carotenoid, and chlorophyll pigments of these plants. The high contents of pigments and the appropriate spectrophotochemical properties make the extracts of these tinctorial plants to become potential raw materials that are useful in solar energy technology.